2006
DOI: 10.1159/000092459
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prenatal Diagnosis of Aneuploidy for Chromosomes 21, 18, 13, and X by Quantitative Fluorescence Polymerase Chain Reaction

Abstract: Objective: Quantitative fluorescence polymerase chain reaction (QF-PCR) is a rapid method for detection of chromosome copy number by amplification of repeat sequences at polymorphic loci. Our objective was to assess the performance of QF-PCR in detecting common aneuploidies in prenatal diagnosis. Study Design: The study group consisted of pregnant women referred for amniocentesis or chorionic villus sampling (CVS) due to increased risk of fetal aneuploidy. Samples were collected from known affected and normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…The difference in the length of the amplified fragment allowed us to determine the gender of a genomic sample [7]. All 48 DNA samples from the controls were correctly diagnosed by the amelogenin gene amplification technique.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the length of the amplified fragment allowed us to determine the gender of a genomic sample [7]. All 48 DNA samples from the controls were correctly diagnosed by the amelogenin gene amplification technique.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Other studies have also concluded that QF-PCR is at least equivalent to interphase FISH for the prenatal detection of aneuploidy. 15,27,30,34 In addition, there are several advantages of QF-PCR over interphase FISH:…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time polymerase chain reaction (qRT-PCR) has recently been used to study unbalanced sets of chromosomes in humans (Zimmermann et al 2002;Ochshorn et al 2006;Tsujie et al 2006), with changes in gene dosage causing significant damage to individuals. Plant molecular biologists have used qRT-PCR to determine the copy number of a transgene (Song et al 2002) and to study polyploidy in Arabidopsis thaliana (Henry et al 2006).…”
Section: Introductionmentioning
confidence: 99%